Dynamics of a brake system governed by modified Burridge-Knopoff-Pad model - Oma Nfor Nkeh; Akoni Brikly Njinabo; Waindim Yisa Tufoin Albert; Kenfack Djifack Hunnel (Heliyon)
Despite widespread investigations to improve on the performance of automobile brake systems, the undesirable phenomenon of disc brake squeal noise remains a very challenging problem to solve. Consequently, we thus propose a basic theoretical brake system based on the modified Burridge-Knopoff-Pad model in this study; in order to elucidate on brake squeal noise and other nonlinear vibrations. Linear stability analysis clearly depicts the stability/instability of some spatial-homogeneous steady states, when some parameters of the system are varied. Our investigation brings into sharp focus the role of nonlinearity, and strongly suggests that the instability of perturbed continuous wave is physically manifested as brake squeal noise. Result of numerical simulations clearly underscores the displacement and velocity profiles of the block-pad brake dynamical system.